Hubungan antara Internal Locus of Control dengan Stres Akademik Pada Mahasiswa Pekerja - Maylia Dwi Pujilestari; Diah Sofiah; Hikmah Husniyah Farhanindya (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to examine the relationship between internal locus of control and academic stress in working students. Working students face simultaneous academic and work demands that can potentially increase academic stress. Internal locus of control is an individual's belief that success and failure are determined by personal effort and ability. This study used a quantitative approach with a correlational design. The subjects were 239 working students at the University of 17 Agustus 1945 Surabaya, selected using a purposive sampling technique. The research instruments included the internality aspect of Levenson's (1981) internal locus of control scale and a modified Gad zella's (1994) Student-Life Stress Inventory (SLSI). Data were analyzed using Spearman correlation with SPSS version 27. The results showed a highly significant negative relationship between internal locus of control and academic stress (r = -0.561; p = 0.001), with a contribution of 74.2%. This finding indicates that the higher the internal locus of control, the lower the academic stress level of working students.